ANALISIS KINERJA SATKER PENGAWASAN SUMBERDAYA KELAUTAN DAN PERIKANAN (PSDKP) DI PELABUHAN PERIKANAN NUSANTARA PALABUHANRATU SUKABUMI JAWA BARAT - Hapsari, Dewi Indri; Rosyid, Abdul; Hapsari, Trisnani Dwi (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Fisheries surveillance of fishing areas are Civil Servants (PNS) were given the duties, responsibilities, authority, rights in full by the competent authorities to conduct surveillance of fishing activities include licensing documents fishing effort, the catch, the crew, loog book fishery , region capture, utilization of fish resources and the environment and other related arrest. The purposes of this study were to identify the functions and roles of PIU PSDKP performance, and analyze the activities of Satker Supervision Analyzing Marine Resources and Fisheries in the Palabuhanratu Nusantara fishing port, Sukabumi, West Java. The method used in this research was descriptive based on case studies. The sampling method used was census. The results obtained performance of Satker Monitoring of Marine Resources and Fisheries has said as well, that is the fundamental duty of each employee would have held but for surveillance at sea can be said to be less good. This is due to the facilities and infrastructure that are not conducive to such monitoring. Need to increase the number of speed boat fleet to support performance monitoring Satker Monitoring of Marine Resources and Fisheries.